OSORS: how do students read online? - Jusoh, Zailani; Abdullah, Liza (Faculty of Languages and Communication, Universiti Sultan Zainal Abidin, 2015)
Success in academia is heavily dependent on the ability of students to capitalise the information available at their disposal through improved reading skills. However, the emergence of digital texts has transformed the nature of academic reading as online reading is reported to be different from traditional printed reading. As such, this paper, based on a study conducted on students in a particular university in Malaysia, was written to explore the extent of the use of strategies when reading online, in an academic setting and also to investigate whether differences in the use of the strategies between male and female students exist. Findings suggest that students are all users of strategies and gender has no bearing on the type of strategies preferred. One of the implications is that class instruction is needed to create awareness on the importance of varied usage of strategies when reading materials online.